Propidium monoazide real‐time loop‐mediated isothermal amplification for specific visualization of viable Salmonella in food. (1st July 2018) - Fang, J.; Wu, Y.; Qu, D.; Ma, B.; Yu, X.; Zhang, M.; Han, J.
Abstract: Traditional DNA‐based molecular detection assays, including loop‐mediated isothermal amplification (LAMP), are unable to differentiate between viable and dead cells. We developed a rapid and accurate method for detection of viable Salmonella cells in food using calcein‐dyed visual real‐time LAMP combined with propidium monoazide (PMA) treatment. Amplification of DNA from up to 6·3 × 10 5 CFU per ml dead Salmonella cells was inhibited by 5 μ mol l −1 PMA dye, whereas the DNA derived from viable cells were detected according the invA gene. In addition, viable Salmonella cells can be directly detected both visually using calcein dye and quantitatively by monitoring amplification curves of fluorescence signals. Both the detection sensitivity of PMA‐LAMP and PMA‐qPCR were 6·3 × 10 2 CFU per ml. The calcein‐dyed visual real‐time PMA‐LAMP assay exhibits high specificity and sensitivity comparable to those of the PMA‐qPCR method and is suitable not only for laboratory research but also for routine screening of viable Salmonella cells in food. Significance and Impact of the Study: Food‐borne illnesses caused by Salmonella spp. threaten public health and food safety. Therefore, it is important to develop a rapid and accurate monitoring method to detect viable Salmonella in food. In this study, we developed a calcein‐dyed visual real‐time loop‐mediated isothermal amplification with propidium monoazide treatment (PMA‐LAMP) in accordance with the above requirements. The method described here could be a valuable tool for routine screening of viable Salmonella in food.